Sociocultural Support Improved Safe Motherhood Practices among Mothers in Three Private Hospitals in Eastern Indonesia - Wirata, Resta Betaliani; Wahyuningsih, Nor Tri Astuti; Richard, Selvia David (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
The importance of sociocultural support from both family and health workers is very much needed by pregnant women until the postpartum period. Utilization of recording facilities using MCH books is not yet optimal in Eastern Indonesia, this is due to the lack of knowledge of midwives, compliance of health workers in filling out MCH books, absence of husbands or family members in caring for pregnant women, taking mothers for pregnancy checks, accompanying them in the birthing process. health services, considering that the mother giving birth at a "dukun beranak" is enough, and involving herself in the postpartum mother's process. This is an obstacle to efforts to deal with maternal and child deaths through safe motherhood. This research method uses a quantitative correlation design with a cross-sectional approach. The population in this study was pregnant and postpartum women registered at 3 private hospitals in Eastern Indonesia totaling 122 mothers. The sampling technique uses total sampling. Data analysis using Chi-Square. The research results show that there is a significant relationship between sociocultural support and safe motherhood practices which has a p-value of 0.004. Good sociocultural support has a high impact on safe motherhood practices to reduce maternal and child mortality from the start.